(untitled) (Bangladesh Journal of Pharmacology, 2011)
The antileishmanial and antimalarial activities of different fractions of Vincetoxicum stocksii, Carum copticum, Gentiana olivierii and Zygophyllum fabago were determined. Amongst these, V. stocksii and C. copticum showed moderate to good antimalarial activity. The ethyl acetate fractions of C. copticum and hexane fraction of V. stocksii showed 94 % and 52% inhibition of Plasmodium falciparum (D6 Clone) respectively. The hexane ethyl acetate fraction of C. copticum and V. stocksi exhibited antileishmanial activity against, Leishmania donovani promastigotes with IC50 of 30 µg/mL and 51 mg/mL, respectively.